Isolation and characterization of Staphylococcus aureus mutants sensitive to Lysozyme by UV radiation - Farah Tarik Abdulkareem; Hameed Majeed (Journal of Madenat Alelem University College, 2012)
Staphylococcus aureus, an opportunistic pathogen commonly found on human skin, were exposed to 1, 2, 3, 4 and 5 J/m2 UV radiation; UV radiation was highly lethal and mutagenic. We detect the mutational effects of irradiation by culturing the isolates on lysozyme containing medium of isolate that was unable to grow in lysozyme and was affected by radiation. Four mutants were obtained and they were sufficiently effective for the isolation of macromolecules such as plasmid and deoxyribonucleic acids, from the cells after lysozyme-induced cell lysis.